Optimal Navigation for First Responders - Kamal Baharin, S. S. (2008)
Decision-making in crisis situations requires a good positional awareness about all the emergency response units (fire brigade, paramedics, police and municipality). Since locations of first responders may change frequently, they are referred as to moving objects. Generally, locations of mo ving objects can be continuously recorded and dynamically visualized (a service available also in command and control software), but still a limited attention is given to real time analysis and simulation. Dedicated software (usually available for one emergency sector and even for a specific region) allows for mo re elaborated route calculations taking into account traffic jams and street blockings, but computations are usually completed for one vehicle and on a predefined road network. In large emergencies, much more complex questions need to be answered such as ‘which ambulance is closer to the place of incident’, ‘how to send in the quickest way three fire trucks to the place of incident’, ‘what is the closest meeting point’, etc. This paper reports initial results on performing complex analysis in a Database Management System (DBMS).